2021
DOI: 10.1136/bmjoq-2021-001369
|View full text |Cite
|
Sign up to set email alerts
|

Early prescribing outcomes after exporting the EQUIPPED medication safety improvement programme

Abstract: Enhancing quality of prescribing practices for older adults discharged from the Emergency Department (EQUIPPED) aims to reduce the monthly proportion of potentially inappropriate medications (PIMs) prescribed to older adults discharged from the ED to 5% or less. We describe prescribing outcomes at three academic health systems adapting and sequentially implementing the EQUIPPED medication safety programme.EQUIPPED was adapted from a model developed in the Veterans Health Administration (VA) and sequentially im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Our study showed comparable directionality of prescribing rates prior to and after the intervention, but the magnitude of change, while significant, was much lower in our study (0.7% vs. 4.8%). When EQUiPPED was first implemented outside of the VA at academic medical centers, only one of the three implementation sites demonstrated significant reduction in PIMs, 30 which was thought to be due to lower baseline PIM proportions when compared to the VA (5.6%–7.3% vs. 7.4%–11.9%). There may be other factors at academic medical centers that yield less significant reductions, such as a large amount of prescribing being initiated by rotating trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed comparable directionality of prescribing rates prior to and after the intervention, but the magnitude of change, while significant, was much lower in our study (0.7% vs. 4.8%). When EQUiPPED was first implemented outside of the VA at academic medical centers, only one of the three implementation sites demonstrated significant reduction in PIMs, 30 which was thought to be due to lower baseline PIM proportions when compared to the VA (5.6%–7.3% vs. 7.4%–11.9%). There may be other factors at academic medical centers that yield less significant reductions, such as a large amount of prescribing being initiated by rotating trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, given that audit and feedback interventions may lead to unintended outcomes, including reduced confidence and cognitive interference,19 20 it may be helpful to prospectively use a theory-driven approach to identify possible unintended outcomes and mitigate the likelihood these occur 20. Although common contextual factors limiting the uptake of evidence are well documented (eg, available resources, values, individual beliefs, past experiences),21–23 how to adapt for contextual variations remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few innovative programs to promote safe medication prescribing, such as Enhancing Quality of Provider Practiced for Older Adults in the Emergency Department (EQUiPPED) program, and the Screening Tool of Older Persons' Prescriptions (STOPP) program and Screening Tool to Alert to Right Treatment (START) program in the literature. 17 , 18 These approaches employ some of the following components: clinician training, clinical decision support, and performance feedback. 17 , 18 Nonetheless, there are persistent knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 These approaches employ some of the following components: clinician training, clinical decision support, and performance feedback. 17 , 18 Nonetheless, there are persistent knowledge gaps. For example, the Beers Criteria await validation in the ED setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation